2013
DOI: 10.1111/1541-4337.12012
|View full text |Cite
|
Sign up to set email alerts
|

Millet Grains: Nutritional Quality, Processing, and Potential Health Benefits

Abstract: In the 21st century, climate changes, water scarcity, increasing world population, rising food prices, and other socioeconomic impacts are expected to generate a great threat to agriculture and food security worldwide, especially for the poorest people who live in arid and subarid regions. These impacts present a challenge to scientists and nutritionists to investigate the possibilities of producing, processing, and utilizing other potential food sources to end hunger and poverty. Cereal grains are the most im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
659
4
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 790 publications
(695 citation statements)
references
References 152 publications
(167 reference statements)
23
659
4
9
Order By: Relevance
“…Carbohydrate content was shown to increase with increase in the concentration of rapoko in the blend. The increase in carbohydrate content was probably due to the nutritional quality of rapoko over maize and this revealed their mutual supplementation effect (Saleh et al, 2013). The processing technologies applied on corn and rapoko grains like fermentation also have a positive outcome on the nutrient content of the product (Onyango et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Carbohydrate content was shown to increase with increase in the concentration of rapoko in the blend. The increase in carbohydrate content was probably due to the nutritional quality of rapoko over maize and this revealed their mutual supplementation effect (Saleh et al, 2013). The processing technologies applied on corn and rapoko grains like fermentation also have a positive outcome on the nutrient content of the product (Onyango et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The processing technologies applied on corn and rapoko grains like fermentation also have a positive outcome on the nutrient content of the product (Onyango et al, 2004). Protein content from 0% to 60% rapoko concentrations increases from 6.80 to 11.95% and this is likely to be due to the addition of rapoko flour (which has a higher protein content over corn) in the blend (Saleh et al, 2013). These results showed that the porridges were nutritious in relation to protein as they provide one third of the Recommended Dietary Allowance (RDA) from 10-12% as recommended by the World Health Organization (Mbata et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations